Vulvitis circumscripta plasmacellularis in pre-existing lichen sclerosus - Han Su Kim; Heung Yeol Kim; Eun Joo Park; Kwang Ho Kim; Kwang Joong Kim (Wolters Kluwer Medknow Publications, 2014)
Vulvitis circumscripta plasmacellularis (VCP) is a rare, benign vulvar disorder that presents with erythematous patches and erosions. Patients with VCP usually experience vulvodynia, pruritus, or dyspareunia, which may cause severe discomfort. A 72-year-old woman presented with 10 years of vulvar pruritus and whitish patches on the labia minora and majora. A biopsy was performed on the labia minora and lichen sclerosus was diagnosed. Her condition improved after treatment with a topical steroid. After 5 months, however, her symptoms reappeared with aggravated skin lesions. A rebiopsy was performed and VCP was diagnosed. There have only been two reported cases of concurrence of VCP with lichen sclerosus. We herein report an unusual case of VCP in pre-existing lichen sclerosus.